KONSEP DIRI REMAJA YANG BERASAL DARI KELUARGA BROKEN HOME (Studi Deskriptif di SMP Negeri 1 Pantai Cermin Kabupaten Solok) - Fauziah, Melda; Kasih, Fitria; Yandri, Hengki (Bimbingan dan Konseling, 2014)
Research was motivated by the numbers of divorce without thinking about the impact on adolescents. The purpose of this research is to investigate and describe the self-concept teenagers who came from a broken home visits of: (1) knowledge aspect, (2) hope aspect and (3) assessment aspect. This research is a qualitative descriptive study. Informants in this research were young 5 people, informants supporting as many as 12 people (5 friends, 5 the mother and 2 teenage counseling teacher). The technique of collecting data through interviews and documentation studies. The accuracy of the data was tested by using triangulation of data, the data were analyzed with an interactive model that consists of data collection, data reduction, data display and conclusion. The research found that adolescents who self-concept comes from a broken home visits of: (1) knowledge aspect, in general adolescents can not accept her family situation and feel hopeless. The tendency is done often aloof, taciturn and morose, also affect daily activities and learning teens, (2) hope aspect, in general, adolescents have good expectations, (3) assessment aspect, low self-esteem of teenage friends others